The Role of Digital Literacy is the Spread of Hoax on Instagram to Strengthen the Character of Unity - Fitrani Rika Asnaria; Achmad Muthali'in; Wibowo Heru Prasetiyo; Patmisari Patmisari (Universitas of Muhammadiyah Makassar, 2022)
The purpose of this study is to describe understanding, perception, and problem solving for a non-medical student applying the digital literacy associated with responding to the hoax of Instagram. The study uses a qualitative approach with a theoretical design. It is often misused to disseminate information quickly but incorrectly. The research informant consists of the study program chairman, lecturer, and student elect using a sampling technique. The data-gathering techniques of this research use interviews, observation, and documentation. The validity test of data uses source triangulation and technical triangulation. Data analysis in this research uses analysis content. According to the study, non-government students have the ability to search out valid information and minimally disseminate hoax information that can lead to conflict. They claim the perception that digital literacy is important to strengthen unity in character. The application of digital literacy is important for finding the right news, making it easy to get the full information, and making a significant contribution to minimizing the spread of hoaxes in Instagram use, as well as an integral part in strengthening the character of unity, thus reducing the impact of the spread of hoax information that could divide the nation. At first glance, students have the digital literacy ability to respond to hoaxes by finding out the truth first though.